2011
DOI: 10.1073/pnas.1004720108
|View full text |Cite
|
Sign up to set email alerts
|

Signal processing in cellular clocks

Abstract: Many biochemical events within a cell need to be timed properly to occur at specific times of day, after other events have happened within the cell or in response to environmental signals. The cellular biochemical feedback loops that time these events have already received much recent attention in the experimental and modeling communities. Here, we show how ideas from signal processing can be applied to understand the function of these clocks. Consider two signals from the network sðtÞ and rðtÞ, either two var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…Experimental evidence suggests that the thermal stability of the protein and the temperature dependent splicing of its mRNA play an important role in temperature compensation (45,46). Simple mathematical models based on Goodwin's oscillator (45,48) have already shown that these mechanisms can impart temperature compensation. Similarly in mammalian circadian clocks, the Per1 gene provides negative feedback and has been implicated in temperature compensation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that the thermal stability of the protein and the temperature dependent splicing of its mRNA play an important role in temperature compensation (45,46). Simple mathematical models based on Goodwin's oscillator (45,48) have already shown that these mechanisms can impart temperature compensation. Similarly in mammalian circadian clocks, the Per1 gene provides negative feedback and has been implicated in temperature compensation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the HT models [91][92][93] Hill exponent is critical for HT models to generate rhythms ( Fig. 2b), a large number of phosphorylation sites at the activator (WCC) is required in Neurospora.…”
Section: Conditions For Rhythm Generationmentioning
confidence: 99%
“…In particular, for both models, it has been shown that the logarithmic sensitivity should be greater than 8 at the steady state (see Appendix for detailed analysis) [34,59,[91][92][93]. Importantly, conditions to achieve such high logarithmic sensitivity differ depending on the repression mechanisms (Figs.…”
Section: Conditions For Rhythm Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetry among elements within a feedback loop was predicted to increase the occurrence likelihood of oscillations [35]. It is, therefore, interesting to study how the degradation rates affect systems dynamics in our dual-feedback context.…”
Section: Dynamics Partitioning Revealed Differential Oscillations-redmentioning
confidence: 99%